PORQUÉ PERMANECER EN ESTE TRABAJO CAUSALES DE LA INTENCIÓN DE SALIDA - Aguirre, Luis Roberto Domínguez; Fernández, José Sergio; Roncancio, Patricia Roncancio; Jiménez, Israel Lozano (European Scientific Journal, ESJ, 2014)
This article aims to show the results of the review of literature of relevant studies of the causal elements of intention to quit in the last five years (2009-2013). The method used to evaluate the literature of the present work was based on the seven steps for research synthesis: problem formulation, literature search, obtaining information from studies, quality assessment studies, analysis and integration of results, interpretation of evidence and presentation of results. 48 studies from 15 different countries with a sample of 35804 employees of different companies were evaluated. The findings suggest the existence of 89 different variables influencing the intended departure of employees in an organization.